DEVELOPING AN INDIVIDUALIZED TREATMENT PLAN FOR DENTAL PATIENTS WITH ACCOMPANYING SENSITIZATION TO BACTERIA, FOOD, POLLEN, AND MORE - Mariana Cekova-Yaneva; Iliyana Stoeva-Ivanova; Georgi S. Nikolov (Peytchinski Publishing, 2020)
Contemporary dental medicine offers a wide range of materials and techniques for the rehabilitation of the dentomaxillofacial system, which in recent years has led to a dramatic increase in allergic reactions in sensitized patients after dental treatment. Once in the oral cavity, saliva and gastrointestinal tract, dental medication or dental material release products that, under certain conditions, can cause direct cell damage or induce an immunological/allergic reaction. The local and systemic reactivity in each individual is different and this explains why biocompatible materials that persist in the oral cavity elicit an immune/allergic response in some patients while none is evident in others. Dental medications, and especially materials that permanently remain in the oral cavity (composites, plastics, metal alloys, etc.), cause hypersensitivity reactions mainly of type IV (slow) and less often of type I (fast). It is very important to develop an individualized treatment plan for dental patients with accompanying sensitization to bacteria, food, pollen, and more. There is no doubt that the implementation of a holistic approach in the treatment of sensitised patients is a prerequisite for a much more successful treatment performed by the dentist. This imposes work in close collaboration with an interdisciplinary team using the possibilities of the modern achievements of immunology and allergology. Patients' history data and the results from skin allergy tests are the basis of application of individualized treatment approach and personalized immunotherapy for each separate patient, as well as of treatment result control.